REPRESENTASI DAKWAH ISLAM DALAM FILM QODRAT 2: ANALISIS SEMIOTIKA ROLAND BARTHES - Misroji; Muhammad Yasir Shofiyurrohman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study analyzes the representation of Islamic dawah in the film Qodrat 2 (2025) using Roland Barthes's semiotic analysis method. This research highlights how dawah messages are constructed through two layers of signification: denotation, connotation, and myth. This qualitative study employs content analysis techniques, examining the themes of visual scenes, dialogue, and religious symbols reported in the film. Data were collected from selected key scenes representing three core dimensions of Islam: Aqidah, Syariah, and Akhlak. The findings show that the representation of Islamic dawah in Qodrat 2 is built reflectively and contextually through spiritual conflicts and character transformations. Aqidah emphasizes the purity of tawhid, Syariah represents worship as a complex psychological struggle, and Akhlak displays social morality. The film functions as a dawah medium that is not only informative but also deeply reflective.